Penerapan Metode System Usability Scale (SUS) Pada Aplikasi Gesiwan Sebagai Media Pembelajaran - Zahra, Lisa; Saputra, Ariansyah; Joni M, A. Bahri (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
The life cycle of animals is a topic considered difficult for students to understand due to the abstract nature of the processes of shape changes and life phases of animals, as well as a lack of conceptual knowledge, making it challenging for students to remember the learning material. Educational games have become a primary focus in improving learning outcomes across various educational levels. By leveraging interactive technology, educational games not only facilitate an enjoyable learning process but also provide opportunities to develop skills and creativity in learning. This educational game is developed using Unity 2021 software. Testing results show that the average SUS score for the GESIWAN (Educational Game on Animal Life Cycles) application is 80.53, which is generally categorized as â€œExcellent.â€ It can be concluded that this interactive multimedia educational game is suitable for use as a learning medium in Grade V at SDN 180 Palembang. This research focuses on analyzing the application of usability in improving user satisfaction with the GESIWAN application. Testing was conducted with student respondents using the SUS (System Usability Scale) method. The goal of this research is to produce an interactive multimedia educational game application by analyzing the gameâ€™s usability that can be used as a learning medium, using the SUS (System Usability Scale) method.